Electrical properties of solution processed layers based on Ge-Si alloy nanoparticles - Meric, Zeynep; Mehringer, Christian; Jank, Michael. P. M.; Peukert, Wolfgang; Frey, Lothar (MRS Advances, 2016)
Ge-Si alloy nanoparticles (NPs) covering the full range of compositions were studied in regard to their suitability as semiconducting channel layer in thin-film transistors (TFTs). Special focus is given to the influence of annealing and encapsulation techniques on the contact and channel properties. Therefore, electrical characterization methods separating contact from channel characteristics are highlighted and applied. It is demonstrated that appropriate passivation of the nanoparticle surfaces can improve the Ion/Ioff ratios by modulation of the density of free charge carriers and also can suppress hysteresis effects. Ge-rich NP alloys can generally be passivated more effectively regardless if passivation is done with solution-processed poly(methyl methacrylate) (PMMA) or by aluminum oxide (Al2O3) from Atomic Layer Deposition (ALD). Sufficient annealing improves the contact formation between aluminum electrodes and Ge-Si particles by modification of charge injection. The presented analysis leads to a better understanding interface and surface effects in porous nanoparticle semiconductors for application in TFT devices.
Keywords: thin film; passivation; nanostructure